La geopolítica y los procesos de integración: Colombia-Nicaragua (2018)
This article is part of a research about integration agreements signed by Colombia. The objective is to explore the future of the Colombian and Nicaraguan agreement inside a strategy of regional integration, it is under the new geopolitical scenario emerged from the sentence of the La Haya about the favor of marine waters to the Central American Country. The methodology used is to review the theory about integration, geopolitics and the different agreements signed for both Co-lombia and Nicaragua. The article evidences that originated new power relations in the region af-ter the International Court of Justice pronouncement. In this sense, it proposes some cooperation actions between countries of the zone and the need to review the terms of the business agreement, which will expire on September 2019.